New Dimensions in Code-Mixing and the Sri Lankan Case: An Exploratory Study - Mawelle, I.J. (My University, 2019)
Code-switching and code-mixing, two by-products of language contact situations, are widely used linguistic strategies, not only in informal conversational contexts but also in the informal media discourse. The reasons hitherto applicable for the mixing of codes seem non-relevant in some code-mixing situations today. This is true to certain segments of the Sri Lankan media context, too, in that the popular Sri Lankan commercial broadcasting media is accused by prescriptivist groups of making excessive use of code-mixing. The purpose of this paper is to synthesize and explore the seminal research articles available in the field of code alternation so as to better understand the Sri Lankan situation of code-switching and code-mixing, as practiced by its general bilingual populations and by the popular commercial media channels.